2024
DOI: 10.3390/ani14010170
|View full text |Cite
|
Sign up to set email alerts
|

Over 300 km Dispersion of Wild Boar during Hot Summer, from Central Poland to Ukraine

Bartłomiej Popczyk,
Daniel Klich,
Paweł Nasiadka
et al.

Abstract: The movement of wild boars is a complex process influenced by both internal conditions and external factors. Despite their typically sedentary lifestyle, dispersion constitutes an integral element of the wild boar’s behavior. This report documents the longest observed wild boar dispersal, involving a collared two-year-old male near Warsaw, Poland. The aim of this study was to present the characteristics of movement during the “nomadic phase”, drawing comparisons with the “sedentary phase”. The other aim was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This is because the first detection of OvGHV2 in free-ranging wild boars occurring in trapped animals was diagnosed within the adjacent municipality of Castro in 2017 [ 39 ], while sampling for the current study occurred between October 2017 and May 2018. A study that evaluated the movement of wild boars estimated that the distance travelled may vary from 76 km (average 1 km/day) during the resting (sedentary) phase to as far as 310 km (average 6 km/day) during the dispersion phase [ 57 ]. Alternatively, another investigation that used the continuous-time speed- and distance-estimation method demonstrated that male wild boars can travel for an average of 5.86 km/day, with females traveling 5.13 km/day [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the first detection of OvGHV2 in free-ranging wild boars occurring in trapped animals was diagnosed within the adjacent municipality of Castro in 2017 [ 39 ], while sampling for the current study occurred between October 2017 and May 2018. A study that evaluated the movement of wild boars estimated that the distance travelled may vary from 76 km (average 1 km/day) during the resting (sedentary) phase to as far as 310 km (average 6 km/day) during the dispersion phase [ 57 ]. Alternatively, another investigation that used the continuous-time speed- and distance-estimation method demonstrated that male wild boars can travel for an average of 5.86 km/day, with females traveling 5.13 km/day [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because these conservation units are located approximately 25 and 50 km away from the center of the municipalities of Ponta Grossa and Palmeira, respectively, as well as 50 km from the center of Castro, where the previous detection was confirmed ( Figure 3 ). These three municipalities, and consequently the surrounding sheep-farming regions, are within the estimated sedentary and dispersion distances travelled by wild boars [ 57 ]. In addition, the Central-eastern mesoregion where these wild boars were infected has the largest sheep population within the State of Paraná [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation